Personality and politics : problems of evidence, inference, and conceptualization : with a new preface - Greenstein, Fred I. (Princeton, New Jersey : Princeton University Press, 1987)
Fred Greenstein, an acknowledged authority in this field, lays out conceptual and methodological standards for carrying out personality-and politics inquiries, ranging from psychological case studies of single actors, through multi-case analyses of types of political actors, to aggregative analyses of the impact of individuals and types of individuals on political systems and processes. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist.
IV. The State of the Personality-And-Politics Literature; A Classification of Types of Personality-And-Politics Inquiry: Individual, Typological, and Aggregative Analyses; 2 : Objections to the Study of Personality and Politics; Cover; I. The Study of Authoritarianism.
Reprint. Originally published: New York : Norton, 1975, ©1969. (The Norton library; N767).
Includes indexes.
Includes bibliographical references (pages 154-184).
Print version record.
eBooks on EBSCOhost
Keywords: Political psychology; Personality; Inference; Psychologie politique; Personnalité.; Inférence (Logique); POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; PHILOSOPHY -- Political; Inference; Personality; Political psychology